Characterization of Mangifera indica cultivars in Thailand based on macroscopic, microscopic, and genetic characters - Aunyachulee Ganogpichayagrai; Kanchana Rungsihirunrat; Chanida Palanuvej; Nijsiri Ruangrungsi (Wolters Kluwer Medknow Publications, 2016)
Thai mango cultivars are classified into six groups plus one miscellaneous group according to germplasm database for mango. Characterization is important for conservation and the development of Thai mango cultivars. This study investigated macroscopic, microscopic leaf characteristics, and genetic relationship among 17 cultivars selected from six groups of mango in Thailand. Selected mango samples were obtained from three different locations in Thailand (n = 57). They were observed for their leaf and fruit macroscopic characteristics. Leaf measurement for the stomatal number, veinlet termination number, and palisade ratio was evaluated under a microscope attached with digital camera. DNA fingerprint was performed using CTAB extraction of DNA and inter-simple sequence repeat (ISSR) amplification. Forty-five primers were screened; then, seven primers that amplified the reproducible band patterns were selected to amplified and generate dendrogram by Unweighted Pair-Group Method with Arithmetic Average. These selected 17 Thai mango cultivars had individually macroscopic characteristics based on fruits and leaves. For microscopic characteristics, the stomatal number, veinlet termination number, and palisade ratio were slightly differentiable. For genetic identification, 78 bands of 190-2660 bps were amplified, of which 82.05% were polymorphic. The genetic relationship among these cultivars was demonstrated and categorized into two main clusters. It was shown that ISSR markers could be useful for Thai mango cultivar identification.